Are health inequalities really not the smallest in the Nordic welfare states? A comparison of mortality inequality in 37 countries. Issue 5 (5th February 2013) - Popham, Frank; Dibben, Chris; Bambra, Clare
Abstract : Background: Research comparing mortality by socioeconomic status has found that inequalities are not the smallest in the Nordic countries. This is in contrast to expectations given these countries' policy focus on equity. An alternative way of studying inequality has been little used to compare inequalities across welfare states and may yield a different conclusion. Methods: We used average life expectancy lost per death as a measure of total inequality in mortality derived from death rates from the Human Mortality Database for 37 countries in 2006 that we grouped by welfare state type. We constructed a theoretical 'lowest mortality comparator country' to study, by age, why countries were not achieving the smallest inequality and the highest life expectancy. We also studied life expectancy as there is an important correlation between it and inequality. Results: On average, Nordic countries had the highest life expectancy and smallest inequalities for men but not women. For both men and women, Nordic countries had particularly low younger age mortality contributing to smaller inequality and higher life expectancy. Although older age mortality in the Nordic countries is not the smallest. There was variation within Nordic countries with Sweden, Iceland and Norway having higher life expectancy and smaller inequalities than Denmark and Finland (for men). Conclusions: Our analysis suggests that the Nordic countries do have the smallest inequalities in mortality for men and for younger age groups. However, this is not the case for women. Reducing premature mortality among older age groups would increase life expectancy and reduce inequality further in Nordic countries.